2017
DOI: 10.1242/jeb.146548
|View full text |Cite
|
Sign up to set email alerts
|

A new cue for torpor induction: charcoal, ash and smoke

Abstract: Recent work has shown that the use of torpor for energy conservation increases after forest fires in heterothermic mammals, probably in response to the reduction of food. However, the specific environmental cues for this increased torpor expression remain unknown. It is possible that smoke and the novel substrate of charcoal and ash act as signals for an impending period of starvation requiring torpor. We therefore tested the hypothesis that the combined cues of smoke, a charcoal/ash substrate and food shortag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 43 publications
1
22
1
Order By: Relevance
“…Organisms that depend on fire‐disturbance for their long‐term survival may be regarded as adapted to fire‐prone habitats (Hutto et al, ; Pausas & Parr, ), although the evidence for unique fire adaptations in animals has rarely been explored (Nimmo et al, ). Recent studies (Stawski et al, , ; Matthews et al, ; Nowack et al, ) indicate that torpor (a state of decreased physiological activity) is used extensively among terrestrial mammals in Australia to deal with fires, or the scorched postfire environment, suggesting that fire may act as a signal, and leads to adaptive changes in animal behaviour and physiology. There are also many pyrophilous fungi species (Robinson, Mellican & Smith, ), i.e.…”
Section: Fire As An Evolutionary Driver Of Biodiversitymentioning
confidence: 99%
See 1 more Smart Citation
“…Organisms that depend on fire‐disturbance for their long‐term survival may be regarded as adapted to fire‐prone habitats (Hutto et al, ; Pausas & Parr, ), although the evidence for unique fire adaptations in animals has rarely been explored (Nimmo et al, ). Recent studies (Stawski et al, , ; Matthews et al, ; Nowack et al, ) indicate that torpor (a state of decreased physiological activity) is used extensively among terrestrial mammals in Australia to deal with fires, or the scorched postfire environment, suggesting that fire may act as a signal, and leads to adaptive changes in animal behaviour and physiology. There are also many pyrophilous fungi species (Robinson, Mellican & Smith, ), i.e.…”
Section: Fire As An Evolutionary Driver Of Biodiversitymentioning
confidence: 99%
“…It is now known that fire has been a leading determinant of species diversity in fire‐prone ecosystems over the last 100 million years (Simon et al, ; Bytebier et al, ; Crisp et al, ; He, Lamont & Downes, ; He et al, ; He et al, ), and has led to the development of an extraordinary diversity of plants (Rundel et al, ). Studies on fire‐stimulated responses under a wide range of fire regimes, and on the role of fire in the ecology and evolution of non‐plant groups (fungi, insects, birds and mammals), are emerging (McMullan‐Fisher et al, ; Hutto et al, ; Stawski et al, ; Pausas & Parr, ; Carbone et al, ). The long co‐existence between these organisms and fire suggests that they have adaptive traits allowing them to persist in fire‐prone environments.…”
Section: Introductionmentioning
confidence: 99%
“…It also adds to a growing body of literature concerning the response of wildlife to changing fire regimes. Recent work has suggested that fire is likely a prominent feature in the evolutionary history of Antechinus, finding that smoke and a substrate of ash and charcoal may act as a cue for the onset of torpor in A. flavipes (Stawski et al, 2017). However, in contrast to congeners (see Aberton, 1996, Fox, 1982, Wilson et al, 2001, our results indicate that long-unburnt vegetation is important for A. argentus.…”
contrasting
confidence: 56%
“…Most likely, the species is climatically confined. As global temperatures rise, these habitats are expected to retract further upwards along elevational gradients (La Sorte and Jetz, 2010 Unlike populations of some other Antechinus species that can endure fire in situ (such as A. stuartii in Guy Fawkes River National Park, NSW) (Stawski et al, 2015, Stawski et al, 2017, the present study found that A. argentus apparently has a preference for relatively long-unburnt habitat. This conclusion is drawn from regular trapping data from the isolated Kroombit…”
Section: Conservation Recommendationsmentioning
confidence: 56%
See 1 more Smart Citation